The role of ETIAS and EES digital systems in the reintegration of veterans and reconstruction of Ukraine: prospects and challenges ETIAS and EES - Hlovatskyi, Yurii (Луцьк: Вежа-Друк, 2024)
The reconstruction of Ukraine and the reintegration of veterans are critical issues following the extensive conflict in the region. The European Travel Information and Authorization System (ETIAS) and the Entry/Exit System (EES), while primarily designed to enhance security and streamline travel procedures, also hold significant potential to contribute to the reintegration of Ukrainian veterans and the reconstruction of Ukraine. These theses explore the prospects and challenges associated with leveraging ETIAS and EES to support these crucial goals.
Keywords: The European Travel Information and Authorization System; Entry/Exit System (EES); the reconstruction of Ukraine; the reintegration of Ukrainian veterans; 338.2:330.34:339.9](06)